Aluminum composite material containing metal and / or ceramic and graphite and method for producing aluminum composite material containing metal and / or ceramic and graphite

By impregnating the melt of aluminum metal or aluminum alloy into the molded body formed from graphite powder, metal powder and/or ceramic powder, the problem of insufficient strength and thermal conductivity of the existing carbon graphite-based materials and aluminum metal composite materials is solved, and the manufacturing of aluminum composite materials with high strength, low thermal expansion coefficient and high thermal conductivity is realized, simplifying the process and reducing costs.

CN119654432APending Publication Date: 2025-03-18ADVANCE COMPOSITE CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380057879.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-11
Filing Date
2023-08-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing composite materials of carbon graphite-based materials and aluminum metals have shortcomings in strength and thermal conductivity, and the manufacturing process is complicated and difficult to widely use.

Method used

By combining the molded body with voids, an aluminum composite material containing metal and/or ceramic and graphite is impregnated into the molded body formed of mixed powders of graphite powder, metal powder and/or ceramic powder by melting an aluminum metal or aluminum alloy, and an inorganic binder of a silica system is added to improve the strength and thermal conductivity of the molded body.

Benefits of technology

Aluminum composite materials with high strength, low thermal expansion coefficient and high thermal conductivity are realized, which simplifies the manufacturing process, reduces the manufacturing cost, and can be widely used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261778280000281
    Figure BDA0005261778280000281
  • Figure BDA0005261778280000291
    Figure BDA0005261778280000291
Patent Text Reader

Abstract

The invention relates to an aluminum composite material containing metal and / or ceramic and graphite, which is formed by compounding a carbon-graphite material and an aluminum material, has high strength, high heat conductivity coefficient and low thermal expansion coefficient, and can be widely used in industry, and provides a technology for developing the material. The present invention relates to an aluminum composite material containing a metal and / or a ceramic and graphite and a method for producing the composite material, the aluminum composite material containing a metal and / or a ceramic and graphite being obtained by compositing a molded body using a melt of an aluminum metal or an aluminum alloy, a metal and / or ceramic and graphite-containing aluminum composite material which is formed from a material obtained by adding a silica-based binder to the outside of a mixed powder that contains a graphite powder that is not amorphous and a metal powder and / or a ceramic powder, and which has a bending strength of 90 MPa or more. The thermal conductivity in either the XY direction or the Z direction is 240 W / m.K or more, and the thermal expansion coefficient in either the XY direction or the Z direction is 6.0 ppm / K or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aluminum composite material containing metal and / or ceramic and graphite and a method for producing the aluminum composite material containing metal and / or ceramic and graphite. More specifically, the present invention relates to a technology for providing an aluminum composite material containing metal and / or ceramic and graphite that exhibits high strength, high thermal conductivity and low thermal expansion coefficient. Background Art

[0002] Carbon and graphite materials are used in many aspects as excellent industrial materials due to their light weight, high thermal conductivity, high electrical conductivity or excellent functionality such as heat resistance and chemical resistance, and they can be easily processed, are cheap and easily available in large quantities. Recently, research and development of composite materials that give carbon or graphite materials the characteristics of metals, such as composite materials made by infiltrating aluminum alloys into graphite, CFRP (carbon fiber reinforced plastic) made by compounding carbon fibers and plastics, and CMC made by compounding carbon ceramics, have been continuously progressing and have begun to be put into practical use.

[0003] Graphite materials other than carbon fiber are manufactured by forming and calcining powders such as coke, but due to their low strength, they are not used as structural materials for mechanical components. In addition, although they are raw materials with high thermal conductivity, they have low thermal conductivity compared to copper and aluminum, so their use as heat dissipation components is also limited. Therefore, it is expected that the properties of graphite materials can be improved so that they can be applied to structural components and heat dissipation components. As technologies that can use graphite for heat dissipation components, for example, there are the following technologies.

[0004] For example, the power module for electrical control used in recent electric vehicles, high-speed railways, etc. has the following structure: a silicon semiconductor element is joined to a substrate as an insulator made of resin or ceramic, and a heat dissipation material such as a copper plate or graphite with excellent thermal conductivity and heat dissipation is joined to the lower part to dissipate the heat generated by the silicon semiconductor. However, if there is a difference in thermal expansion coefficient between the silicon semiconductor and the insulator (substrate) and the heat dissipation material, or if the strength of the heat dissipation material is low, stress caused by the difference in thermal expansion coefficient is generated at the joint surface between the insulator (substrate) and the heat sink, and sometimes cracks are generated. Specifically, when the heat sink is made of copper, the difference in thermal expansion coefficient is large, so there is a problem of cracking. In addition, when the heat sink is made of graphite, there is a problem of rupture and cracking caused by insufficient strength of graphite.

[0005] In addition, in recent years, semiconductors used in power modules have been replaced by semiconductors using SiC single crystals or gallium nitride single crystals with larger electrical band gaps, rather than silicon semiconductors using silicon wafers in the past. However, it is known that the heat generated when using conventional silicon semiconductors is about 100°C, while when using SiC semiconductors and gallium nitride semiconductors, the operating temperature is higher, about 200°C. Therefore, if a raw material with a thermal expansion coefficient closer to that of the semiconductor material of SiC and gallium nitride can be provided as a material for a substrate or heat sink disposed under a SiC semiconductor or gallium nitride semiconductor, a more excellent power module can be provided.

[0006] Specifically, as a material for a substrate or heat sink disposed at the bottom of a semiconductor, it is desired to provide a raw material that has a low thermal expansion coefficient, for example, close to the thermal expansion coefficient of 4 to 6 ppm / K of SiC, gallium nitride, etc., which is a material of the above-mentioned semiconductor, in addition to having sufficient strength and thermal conductivity, and is high strength and high thermal conductivity. In contrast, since a general and economical raw material that satisfies all the required performances as described above is not known alone, it is desired to develop a composite material. Here, in the case of applying a composite material as a substrate or heat sink disposed at the bottom of a semiconductor, it is sufficient as long as the thermal expansion coefficient in any direction of the XY direction or the Z direction is close to that of the semiconductor. That is, in the case of using a substrate or heat sink formed by a composite material, for example, if a composite material whose thermal expansion coefficient in the XY direction is close to that of the semiconductor is used and is bonded to a semiconductor, etc. in its XY direction, the function of the composite material can be fully exerted.

[0007] As described above, as a practical composite material that can be applied to a substrate or heat sink disposed under a semiconductor such as SiC or gallium nitride, it is desirable to develop a raw material that exhibits high strength, low thermal expansion coefficient, and high thermal conductivity. Specifically, it would be extremely useful to provide a new raw material that satisfies all the conditions of having a practical bending strength of 90 MPa or more, a thermal expansion coefficient of 6 ppm / K or less in either the XY direction or the Z direction, and a thermal conductivity of 240 W / m·K or more in either the XY direction or the Z direction.

[0008] Among them, the development of composite materials of graphite materials and aluminum metal is underway. As one of the methods, a method of infiltrating aluminum alloy into the pores of a molded body made of carbon (carbonaceous) or graphite materials (hereinafter also referred to as carbon graphite materials) is proposed, and there are also practical methods. For example, Patent Document 1 proposes a carbon-based metal composite material in which more than 90% by volume of the pores of a carbonaceous matrix containing graphite crystals are replaced by metal components such as aluminum and magnesium. In addition, a manufacturing method of pressurized infiltration of molten metal in a carbon molded body having a porosity of less than 40% by volume is proposed. Moreover, according to the technology proposed in Patent Document 1, a composite material with a thermal conductivity of more than 150W / m·K can be obtained.

[0009] Patent document 2 proposes a carbon-based metal composite material formed by pressurizing aluminum metal or aluminum alloy into a carbon molded body with a porosity of 35% or less containing graphitized carbon particles by melt forging. This composite material is considered to be useful for electronic device substrates with high thermal conductivity, low thermal expansion coefficient and low elastic modulus. In addition, Patent document 3 proposes an electrode material for discharge machining formed by infiltrating an Al alloy containing more than 10% Si component into a graphite material by melt forging or HIP method. Patent document 4 proposes a metal-graphite composite material suitable for two-dimensional diffusion of heat and having high thermal conductivity in a biaxial direction.

[0010] In addition, Patent Document 5 proposes the following technology: a powder of carbide such as titanium carbide, a powder of oxide such as titanium oxide, or a powder of metal titanium is mixed with coke powder or a mixed powder of coke powder and graphite powder, tar or pitch is added to the mixed powder to make a paste, extrusion molding is performed, and a solid is obtained by once calcining at 1000 to 1500°C, and tar or pitch is impregnated into the obtained solid by applying pressure, and the first calcination at 1000 to 1500°C is repeated multiple times, and then a final calcination at 2500 to 3000°C is performed to obtain an extruded body, and aluminum is impregnated into the obtained extruded body under pressure to prepare an aluminum-graphite-carbide composite. Moreover, according to the above technology, a composite body with improved fragility and suitable thermal conductivity is obtained.

[0011] In addition, Patent Document 6 proposes a plate-like aluminum-silicon carbide composite and a method for manufacturing the composite, wherein the plate-like aluminum-silicon carbide composite is obtained by adding silicon carbide powder to "artificial graphite powder obtained by graphitizing coke-based carbon" and pressing to obtain a molded body, and in the molded body, aluminum or aluminum alloy is infiltrated under high pressure. This technology makes it possible to obtain a composite material having characteristics such as low thermal expansion and high thermal conductivity. Moreover, in Patent Document 7, a molded body is obtained by adding silicon carbide powder and boron nitride powder to "artificial graphite powder obtained by graphitizing coke-based carbon" and pressing to obtain a molded body, and aluminum or aluminum alloy is infiltrated under high pressure in the molded body, thereby enabling the plate-like aluminum-silicon carbide composite to have good processability on the basis of having the above-mentioned effects. In these documents, as artificial graphite powder, artificial graphite powder with an average particle size of 1 to 1000 μm is used.

[0012] Furthermore, Patent Document 8 proposes an aluminum-graphite-silicon carbide composite and a method for producing the composite, wherein the aluminum-graphite-silicon carbide composite is formed by pressurizing and infiltrating aluminum or an aluminum alloy into a molded body containing graphite powder and silicon carbide powder by a molten forging method. In addition, it is disclosed that in addition to using "artificial graphite powder obtained by graphitizing coke-based carbon" as in Patent Documents 6 and 7, a portion or all of the graphite powder is used as "flaky graphite powder". "Artificial graphite powder obtained by graphitizing coke-based carbon" is amorphous, and "flaky graphite powder" is a graphite powder having a crystalline structure.

[0013] In addition, Patent Document 9 proposes a heterogeneous composite material having an integral structure formed by placing preforms formed of two different reinforcing materials adjacent to each other and infiltrating and casting molten metal such as aluminum under high pressure. In addition, a heterogeneous composite material having an integral structure formed by placing a preform formed of silicon carbide particles adjacent to a preform formed of graphite, or placing a preform formed of alumina particles adjacent to a preform formed of carbon fibers, and infiltrating and casting molten metal that becomes a matrix under high pressure is described. In addition, Patent Document 9 describes that if the reinforcing material is ceramic, even a material formed by adding an inorganic binder such as silica sol or alumina sol can be used.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent No. 3673436

[0017] Patent Document 2: Japanese Patent No. 3351778

[0018] Patent Document 3: Japanese Patent Application Publication No. 2004-209610

[0019] Patent Document 4: Japanese Patent No. 4441768

[0020] Patent Document 5: Japanese Patent No. 6722089

[0021] Patent Document 6: Japanese Patent No. 5208616

[0022] Patent Document 7: Japanese Patent No. 5368766

[0023] Patent Document 8: Japanese Patent No. 5061018

[0024] Patent Document 9: Japanese Patent No. 4384830 Summary of the invention

[0025] Problem that the invention aims to solve

[0026] As described above, various schemes for composite materials of carbon graphite-based materials and aluminum metal have been proposed so far, and composite materials with high thermal conductivity of more than 150W / m·K have been obtained (see Patent Document 1). However, as described in the prior art listed above (see Patent Document 5, etc.), in the composite materials of carbon graphite-based materials and aluminum metal, it is required to provide a material with improved fragility of the composite, that is, a material with high strength and a high and appropriate thermal conductivity. Although various studies have been conducted, it is still difficult to say that the above aspects have been solved. For example, in the prior art described in Patent Document 5 using coke powder and tar pitch that solves the above problems, it is necessary to repeatedly perform complicated primary calcination at 1000 to 1500°C for many times, and then further perform final calcination at 2500 to 3000°C to obtain an extruded molded body of the intermediate. In this way, in the prior art, in addition to the complicated manufacturing process, a high calcination temperature is required, so the manufacturing cost is incurred, it is difficult to put into practical use, and it is not a technology that can be widely used.

[0027] Among the graphite powders used in composite materials with aluminum and the like in the prior art, there are the following differences between amorphous graphite powder and graphite powder with a crystal structure such as natural graphite powder. For example, when the flaky graphite powder with a crystal structure studied in Patent Document 8 is used as the graphite powder, an aluminum-graphite-silicon carbide composite is obtained in which the thermal conductivity in the direction perpendicular to the forming direction of the formed body is significantly improved. In addition, as described in the table of Patent Document 8, in the case of a composite of amorphous graphite powder such as "artificial graphite powder obtained by graphitizing coke-based carbon", it is impossible to obtain the high thermal conductivity achieved by the composite using flaky graphite powder. On the other hand, in the case of a composite using flaky graphite powder, it is impossible to obtain the high strength as in the case of a composite using amorphous graphite powder.

[0028] In addition, when graphite powder is used in the composite material, in addition to poor formability, there is also the problem of poor shape stability of the molded body (preformed body) used when it is infiltrated with a molten aluminum metal or the like and composited. According to the research of the present inventors, when graphite powder is used in the composite material, in the process after the composite material is pressed and formed to obtain a molded body, the density of the molded body is easily rebounded, so a complicated process is required to suppress the occurrence of rebound. Therefore, there is a major industrial issue that a practical manufacturing method has not yet been obtained. For example, in the embodiments of patent documents 6 to 8 of the prior art, a material using graphite powder is filled into an iron container and a molded body is made by pressing and forming. In order to suppress its rebound, the upper and lower iron plates of the iron container are welded and covered with a lid, so that the molded body obtained thereby is kept in the iron container, and the molten aluminum alloy is infiltrated under high pressure to perform composite.

[0029] Furthermore, as described above, as a practical composite material that can be applied to the substrate and heat sink material provided under the semiconductor such as SiC and gallium nitride used in recent years, it is expected to develop a raw material that satisfies all conditions of high strength, low thermal expansion coefficient and high thermal conductivity, which has a practical bending strength of 90 MPa or more, a thermal expansion coefficient of 6 ppm / K or less in any direction of the XY direction or the Z direction, and a thermal conductivity of 240 W / m·K or more in any direction of the XY direction or the Z direction. In contrast, according to the prior art, such an excellent raw material has not been provided.

[0030] Recently, high-tech carbons such as graphene, fullerene, and carbon nanotubes have attracted attention, and their potential physical properties such as high thermal conductivity have attracted attention. However, the current situation is that these materials are very difficult to handle due to their fine powder, and their utilization methods have not yet been established. It is usually carried out as follows. When a composite material is obtained using fine powder graphite powder, after adding a binder such as tar pitch, extrusion molding and CIP molding are performed, and then calcined at about 3000°C to obtain a graphite block with a void of 5 to 35%, and the graphite block is infiltrated with aluminum molten metal to manufacture. However, in this method, in fact, part of these voids become closed pores due to the binder, etc., so it is difficult to infiltrate metal in all the voids. Therefore, the composite materials that have previously used carbon graphite materials have low strength due to the low strength of graphite itself and the low infiltration amount of metals such as aluminum, aluminum alloy or copper in the composition of the composite material, so their scope of use is limited.

[0031] Therefore, the object of the present invention is to realize an extremely useful aluminum composite material containing metal and / or ceramic and graphite that can be widely used in industry and has the high strength, high thermal conductivity and low thermal expansion coefficient listed above, which is obtained by compounding a mixed powder of crystalline carbon graphite-based materials and metal powder materials and / or ceramic powder materials other than aluminum using a molten aluminum metal or aluminum alloy, and further, to develop a technology that can simply and stably provide the aluminum composite material containing metal and / or ceramic and graphite without the need for complicated processes.

[0032] Solutions for solving problems

[0033] The above object is achieved by the present invention described below. That is, the present invention provides the aluminum composite material containing metal and / or ceramic and graphite described below.

[0034] [1] An aluminum composite material containing metal and / or ceramic and graphite, characterized in that it is a composite material containing metal and / or ceramic and graphite obtained by compounding a molded body having voids with a molten aluminum metal or aluminum alloy, wherein the molded body having voids is a mixed powder to which a silica-based inorganic binder is added, wherein the mixed powder comprises: graphite powder, the graphite powder being composed of natural graphite powder having a non-amorphous crystal structure or artificial graphite powder having a non-amorphous crystal structure; and at least one of metal powder and / or ceramic powder,

[0035] The aluminum composite material containing metal and / or ceramic and graphite contains the graphite powder in a range of 40 to 80 volume %, the aluminum metal or aluminum alloy in a range of 13 to 50 volume %, and the metal powder and / or the ceramic powder in a range of 6 to 45 volume % in total, the total amount of these materials being 100 volume %, and the SiO converted into 2The aforementioned silica-based inorganic binder is externally added in an amount of 0.5 to 5% by volume,

[0036] The aluminum composite material containing metal and / or ceramic and graphite has a bending strength of 90 MPa or more, a thermal conductivity of 240 W / m·K or more in any of the XY direction or the Z direction, and a thermal expansion coefficient of 6.0 ppm / K or less in any of the XY direction or the Z direction.

[0037] As a preferred embodiment of the aluminum composite material containing metal and / or ceramic and graphite of the present invention, the invention having the following configuration can be cited.

[0038] [2] The aluminum composite material containing metal and / or ceramic and graphite according to the above [1], wherein the thermal conductivity in the XY direction is 240 W / m·K or more, and the thermal conductivity in the Z direction is 50 W / m·K or more, and the thermal expansion coefficient in the XY direction is 6 ppm / K or less, and the thermal expansion coefficient in the Z direction is 19 ppm / K or less.

[0039] [3] The aluminum composite material containing metal and / or ceramic and graphite according to [1] or [2] above, wherein the thermal expansion coefficient in the XY direction is 3 ppm / K or more and 6 ppm / K or less.

[0040] [4] An aluminum composite material containing metal and / or ceramic and graphite according to any one of [1] to [3] above, wherein the silica-based inorganic binder comprises at least one selected from the group consisting of colloidal silica, ethyl silicate, water glass and silicone resin.

[0041] [5] The aluminum composite material containing metal and / or ceramic and graphite according to any one of [1] to [4] above, wherein the average particle size of the graphite powder is 3 μm to 300 μm.

[0042] [6] An aluminum composite material containing metal and / or ceramic and graphite according to any one of [1] to [5] above, wherein the non-amorphous crystal structure is any crystal structure selected from the group consisting of layered crystals, three-dimensional graphite crystals, diamond crystals and fullerene structures.

[0043] [7] The aluminum composite material containing metal and / or ceramic and graphite according to any one of [1] to [6] above, wherein the average particle size of the metal powder and / or the ceramic powder is 0.5 to 200 μm.

[0044] [8] An aluminum composite material containing metal and / or ceramic and graphite according to any one of [1] to [7] above, wherein the metal powder is any one selected from the group consisting of silicon powder, titanium powder, silver powder, copper powder, iron powder, stainless steel and aluminum powder, and the ceramic powder is any one selected from the group consisting of alumina powder, silicon nitride powder, silicon carbide powder and aluminum nitride powder.

[0045] As another embodiment, the present invention provides a method for producing the following aluminum composite material containing metal and / or ceramic and graphite.

[0046] [9] A method for producing an aluminum composite material containing metal and / or ceramic and graphite, characterized in that it has:

[0047] A molding step of molding a molded body, wherein 40 to 80 volume % of graphite powder composed of natural graphite powder having a non-amorphous crystal structure or artificial graphite powder having a non-amorphous crystal structure, 6 to 45 volume % of metal powder and / or ceramic powder, 13 to 50 volume % of voids in the molded body after molding, and the total volume 100 volume % are adjusted to 100 parts by volume of a mixed powder of raw materials, in terms of SiO 2 Adding a silica-based inorganic binder in an amount of 0.5 to 5 parts by volume, forming a molded product with the obtained material, and heating and curing the molded product at a temperature of 100° C. to 1100° C. to prepare a molded body having the aforementioned voids for composite formation; and

[0048] A composite step of infiltrating or pressing a molten aluminum metal or aluminum alloy into the voids of the molded body at a pressure of 20 to 200 MPa to perform composite formation;

[0049] A composite material is manufactured having a bending strength of 90 MPa or more, a thermal conductivity of 240 W / m·K or more in either the XY direction or the Z direction, and a thermal expansion coefficient of 6.0 ppm / K or less in either the XY direction or the Z direction.

[0050] As a preferred embodiment of the method for producing the aluminum composite material containing metal and / or ceramic and graphite of the present invention, the invention having the following configuration can be cited.

[0051]

[10] The method for producing an aluminum composite material containing metal and / or ceramic and graphite according to the above [9], wherein the aforementioned silica-based inorganic binder comprises at least one selected from the group consisting of colloidal silica, ethyl silicate, water glass and silicone resin.

[0052]

[11] The method for producing an aluminum composite material containing metal and / or ceramic and graphite according to the above [9] or

[10] , wherein the method performed in the molding step of the molded body is at least one selected from the group consisting of press molding, filter press pressing, roll molding, CIP molding, sedimentation method and casting molding.

[0053] Effects of the Invention

[0054] According to the present invention, a mixed material of metal and / or ceramic powder and carbon graphite powder having a crystal structure is composited with an aluminum material such as aluminum metal or aluminum alloy (hereinafter also referred to as "aluminum metal, etc.") as a metal material, and an extremely useful aluminum composite material containing metal and / or ceramic and graphite that has high strength, high thermal conductivity, and low thermal expansion coefficient and can be widely used industrially is provided. According to the present invention, repeated calcination at high temperature as in the prior art is not required, and an operation for maintaining the shape of a molded body is not required, and the aluminum composite material containing metal and / or ceramic and graphite (hereinafter also referred to as "graphite composite material") having the above-mentioned excellent characteristics can be stably produced by a simple method, so the graphite composite material having the above-mentioned excellent characteristics can be widely used.

[0055] The purpose of the present invention is to realize a graphite composite material having excellent properties of high strength, high thermal conductivity and low thermal expansion coefficient. The inventors have found that the above purpose can be achieved by manufacturing as follows. First, ceramic powders represented by silicon carbide, aluminum oxide, etc. and / or metal powders such as silicon powder and titanium powder are added to natural graphite powder or artificial graphite powder having a crystal structure that exhibits high thermal conductivity even if it is a single material, and then a silica-based inorganic binder represented by colloidal silica and ethyl silicate is added to obtain a material. In a molded body (preformed body) formed by the obtained material, a melt of aluminum metal, etc. is infiltrated or pressed into it to form a composite, thereby making it possible to produce a graphite composite material with the target excellent properties by a simple method.

[0056] The technical feature of the present invention is that, by adding a silica-based inorganic binder to the mixed powder of the raw materials used in the preparation of the molded body, the problem of using carbon graphite raw materials to make a molded body that is difficult to make even by a molding method that applies pressure, such as press molding, is solved, and a molded body (preformed body) in a good state is made, and then a good composite of the molded body and aluminum metal, etc. is achieved. For example, according to the present invention, by making the raw materials for the preparation of the molded body contain a silica-based inorganic binder, the strength of the molded product formed at room temperature by methods such as press molding can be improved, so that a strong molded body that suppresses the rebound that occurs thereafter can be obtained. Moreover, by adding a silica-based inorganic binder to the mixed powder of the raw materials used in the preparation of the molded body, the following effects can be achieved. First, the molten aluminum metal, etc. at about 700°C is infiltrated into the molded body, which not only suppresses the deformation of the molded body caused by the pressing of the aluminum metal, etc., but also the close fit between the graphite material having a crystal structure and the added metal and / or ceramic powder material is firmly maintained inside the molded body. Furthermore, aluminum metal or the like can be infiltrated and pressed into the molded body in this state to form a composite, thereby achieving a graphite composite satisfying all the properties of high strength, high thermal conductivity, and low thermal expansion coefficient, which is the objective of the present invention. DETAILED DESCRIPTION

[0057] The present invention is described in detail below by listing preferred embodiments. As described above, various methods for impregnating a molten metal material, especially an aluminum material, into a carbon graphite material or a ceramic material under high pressure have been proposed in the prior art. However, these methods cannot be considered as completed technologies, and the following problems have been pointed out.

[0058] The composite material formed by impregnating a molten metal such as aluminum metal in a carbon graphite material has low strength, especially a bending strength as low as 15 to 30 MPa. Therefore, when a mechanical part requiring strength is made, a heat sink requiring thermal conductivity, a heat sink, a heat sink, and other functional parts, there is a problem of insufficient strength of the product. According to the research of the present inventors, the reason is as follows. It is believed that the reason is that the strength of the carbon graphite material used in the composite material is originally low, and even if the molten metal of aluminum metal or the molten metal of copper metal is impregnated into these materials to form a composite, the impregnation amount is as low as about 20% of the total. That is, as described above, a molded product is formed by using a material that generates a carbon binder such as tar pitch in the carbon graphite material, and then the molded body produced by baking is prone to closed pores. When the metal molten metal is impregnated, the metal is not impregnated in the closed pores in a good state, so the impregnation amount is reduced as described above, and the strength increase achieved by metal impregnation cannot be fully obtained.

[0059] In contrast, as described above, an aluminum-ceramic composite having excellent characteristics has been proposed, which is formed by impregnating an aluminum alloy into a molded body, the molded body being formed of a material obtained by mixing silicon carbide powder and, as required, boron nitride powder with amorphous artificial graphite powder obtained by artificially graphitizing coke-based carbon (see Patent Documents 6 to 8). However, in the prior art, a single material or a composite material having not only a practical bending strength of 90 MPa or more and a high thermal conductivity suitable for a base or heat sink for a power module in recent years, but also a low thermal expansion coefficient, specifically a thermal expansion coefficient of 6 ppm / K or less, has not been known.

[0060] The inventors of the present invention have conducted intensive research to solve the problems of the above-mentioned prior art, and as a result, have discovered the aluminum composite material (graphite composite material) containing metal and / or ceramic and graphite of the present invention. Specifically, in a composite of a carbon graphite-based powder material and aluminum metal, etc., by using at least one of non-amorphous and highly crystalline graphite powder, metal powder and / or ceramic powder to enhance strength, a graphite-based composite material having an important characteristic for practical application, namely "easy formability", and capable of achieving a high level of high strength, high thermal conductivity and low thermal expansion coefficient, which is the goal of the present invention, has been discovered, and a manufacturing method capable of manufacturing the composite material simply and at low cost has been discovered, thereby achieving the present invention.

[0061] The graphite composite material of the present invention is a composite of a molded body with voids using a melt of aluminum metal or the like, wherein the molded body with voids has a mixed powder and is added with a silica-based inorganic binder, wherein the mixed powder includes: graphite powder that is not an amorphous crystal structure; and at least one of metal powder and / or ceramic powder. The molded body characterized by the present invention is formed by adding a silica-based inorganic binder in a range of 0.5 to 5 parts by volume to 100 parts by volume of the mixed powder (including voids). The graphite composite material of the present invention has the following material composition: the graphite powder is contained in a range of 40 to 80% by volume, the aluminum metal is contained in a range of 13 to 50% by volume, the metal powder and / or the ceramic powder is contained in a range of 6 to 45% by volume, the total amount of these materials is set to 100% by volume, and further converted to SiO 2 The aforementioned silica-based inorganic binder is added externally in an amount of 0.5 to 5% by volume. The graphite-based composite material of the present invention formed by the above-mentioned materials is characterized in that it exhibits the following excellent properties: its bending strength is 90 MPa or more, and its thermal conductivity in any direction of the XY direction or the Z direction is 240 W / m·K or more, and further, its thermal expansion coefficient in any direction of the XY direction or the Z direction is 6.0 ppm / K or less.

[0062] Examples of preferred properties of the graphite composite material of the present invention include: a bending strength of 90 MPa or more, a thermal conductivity of 240 W / m·K or more in the XY direction, a thermal conductivity of 50 W / m·K or more in the Z direction, a thermal expansion coefficient of 6 ppm / K or less in the XY direction, and a thermal expansion coefficient of 19 ppm / K or less in the Z direction. Among them, a thermal expansion coefficient of 3 ppm / K or more and 6 ppm / K or less in the XY direction is more preferably used.

[0063] Hereinafter, each material constituting the graphite composite material of the present invention will be described.

[0064] (1) Graphite powder

[0065] The graphite powder constituting the graphite composite material of the present invention can be natural graphite powder having a non-amorphous crystal structure or artificial graphite powder having a non-amorphous crystal structure, preferably a powder with high crystallinity. On the other hand, amorphous natural graphite powder and artificial graphite powder cannot be used as the graphite powder constituting the present invention because they have a large thermal expansion coefficient and a low thermal conductivity. As a preferred example of the specific graphite powder constituting the present invention, graphite powders with the following structures can be listed. Natural graphite powder or artificial graphite powder having a layered structure formed by overlapping a 2-dimensional mesh structure in the molecular structure, diamond powder having a 3-dimensional mesh structure, artificial graphite crystal powder, and artificial crystalline nanocarbon connected in a spiral cylindrical shape can be listed. Graphite powder with high crystallinity has high thermal conductivity in the layered direction and a small thermal expansion coefficient in the case of layered crystals, high thermal conductivity in the three-dimensional direction and a small thermal expansion coefficient in the case of diamond powder, and high thermal conductivity in the growth direction and a small thermal expansion coefficient in the case of nanocarbon, so it can be suitable for the graphite composite material of the present invention.

[0066] More specifically, the graphite powder constituting the graphite composite material of the present invention can use any of the crystalline graphite powders listed below, rather than amorphous materials. For example, artificial graphite powder, natural layered graphite powder, natural or artificial diamond powder with diamond structure, and nano-carbon aggregates formed by pre-molding and roasting ultrafine powders to form powders that are easy to handle, which are formed by adding tar pitch and the like to carbon with a layered structure and roasting and pulverizing at about 3000°C or above, can also be used. According to the research of the inventors, relative to the above content, the material formed by mixing organic binders such as tar pitch in coke powder and molding and roasting at 2000°C to 2500°C cannot be used to constitute the graphite powder of the present invention because the carbon does not completely form a layered crystal structure, the thermal expansion coefficient is large, and the thermal conductivity is low. Amorphous carbon obtained by calcining carbon black, tar, or organic resin at low temperature has low strength, low thermal conductivity, and large thermal expansion coefficient. Therefore, even if they are used, it is impossible to obtain a graphite composite material with high strength, high thermal conductivity, and low thermal expansion coefficient, which is the goal of the present invention.

[0067] In addition, as the natural graphite powder with a crystal structure constituting the graphite composite material of the present invention, it is preferred to make scaly graphite or spherical graphite with a layered crystal structure. On the other hand, bulk natural graphite without a layered crystal structure has a low thermal conductivity and is not a graphite with a low thermal expansion coefficient, so it cannot be used as a raw material for the graphite composite material of the present invention.

[0068] The graphite powder having a non-amorphous crystal structure listed above constituting the present invention preferably has an average particle size of 3μm to 300μm. Whether the graphite powder composed of natural graphite powder or artificial graphite powder has a crystal structure that can be used as a raw material for the graphite composite material of the present invention can be easily investigated by X-ray diffraction. Generally, a sharp peak appears when the diffraction angle 2θ is 24 to 28°. According to the research of the present inventors, when the average particle size is less than 3μm, the particles are too fine and difficult to form, and the particle interface becomes wide, and the thermal conductivity of the graphite composite material of the present invention becomes low, so it is not preferred. On the other hand, if the average particle size exceeds 300μm, it is difficult to form by pressing, etc., so it is not preferred in terms of formability. According to the research of the present inventors, the more preferred range of the graphite powder constituting the present invention is an average particle size of 5μm to 250μm, and it is further preferred to use a graphite powder with an average particle size of 10μm to 200μm. If it is within the above range, it is possible to provide a graphite composite material with higher industrial utilization value that can be easily and stably molded in addition to the excellent properties of high strength, high thermal conductivity, and low thermal expansion coefficient as the target of the present invention. It should be noted that the average particle size of the powder used in the present invention refers to the particle size when the cumulative value in the particle size distribution obtained by the laser diffraction / scattering method is 50%. It is the so-called 50% median particle size.

[0069] (2) Metal powder, ceramic powder

[0070] The metal powder and ceramic powder constituting the graphite composite material of the present invention are not particularly limited, and as described later, the average particle size is preferably 0.5 μm to 200 μm. As the metal powder, for example, metal powders having a melting point of about 500°C or above, such as aluminum (Al), silicon (Si), silver (Ag), titanium (Ti), copper (Cu), iron (Fe), and stainless steel (SUS) can be used. Among them, metal powders such as silicon (Si), titanium (Ti), silver (Ag), and copper (Cu) are preferably used. In addition, as the ceramic powder, for example, oxides such as aluminum oxide and silicon dioxide, boron carbide (B 4 C), carbides such as silicon carbide (SiC) and titanium carbide (TiC), nitrides such as silicon nitride and aluminum nitride (AlN).

[0071] The particle size of the metal powder and ceramic powder listed above that constitute the present invention preferably has an average particle size of 0.5 to 200 μm. According to the research of the inventors, when the average particle size is less than 0.5 μm, it is too fine and easy to aggregate, and may not be evenly mixed with the graphite powder used in combination. On the other hand, when using a powder with an average particle size exceeding 200 μm, the particle size is too large and difficult to shape, the moldability is poor, and it is difficult to obtain a high-strength composite, so it is not preferred. According to the research of the inventors, the more preferred range of the metal powder and ceramic powder that constitute the present invention can use a powder with an average particle size of 2 to 150 μm, and it is more preferred to use a powder with an average particle size of 3 to 100 μm.

[0072] (3) Silica-based inorganic binders

[0073] As the silica-based inorganic binder constituting the graphite-based composite material of the present invention, for example, colloidal silica, ethyl silicate, water glass, and silicone resin can be used. 2 The amount of the mixed powder containing the graphite powder as the raw material of the above-mentioned molded body and at least one of the metal powder and / or ceramic powder is added externally in a range of 0.5 to 5 volume % to 100 parts by volume (including voids) for the preparation of the molded body. Preferably, on a volume basis, an amount of about 1% or more and about 5% or less is added externally relative to 100 parts by volume of the above-mentioned mixed powder. According to the research of the inventors, the silica-based inorganic binder is necessary for improving the moldability of the molded body when preparing the molded body formed by the above-mentioned mixed powder, and maintaining the shape of the molded body after the heat curing (baking) of the molded body. That is, as described above, the graphite powder with a crystal structure constituting the graphite-based composite material of the present invention is a layered, three-dimensional mesh structure, so when the molded body is formed in the molding process, the force to restore the molded body, the so-called rebound, is large, so in order to maintain the shape of the molded body after baking, it is necessary to add a silica-based inorganic binder. On the other hand, an organic binder can be used as an auxiliary material during molding in the case of press molding, but since it disappears during the pre-sintering performed when obtaining a molded body (preform), it cannot be used to maintain the shape of the molded body after pre-sintering. In contrast, according to the present invention, by using a graphite powder composed of a natural graphite powder having a crystal structure with poor moldability or an artificial graphite powder having a crystal structure with poor moldability, and adding a silica-based inorganic binder to the forming material of the molded object, it is possible to provide an extremely useful graphite composite material that has high strength, high thermal conductivity and low thermal expansion coefficient at a high level that cannot be achieved in the prior art that the present invention is aimed at, and can be widely used in industry.

[0074] (4) Composition of graphite composite materials

[0075] The graphite composite material of the present invention is characterized in that it is a composite of a molded body having voids using a melt of aluminum metal or the like, wherein the molded body having voids is formed by adding a silicon dioxide-based inorganic binder externally in a range of 0.5 to 5 parts by volume to 100 parts by volume (including voids) of a mixed powder containing the previously listed highly crystalline graphite powder having a crystal structure and at least one of metal powder and / or ceramic powder. Furthermore, the graphite composite material of the present invention is characterized in that it has the following composition: graphite powder is contained in a range of 40 to 80% by volume, aluminum metal is contained in a range of 13 to 50% by volume, and metal powder and / or the aforementioned ceramic powder is contained in a range of 6 to 45% by volume, and the total amount of these materials is set to 100% by volume, and then converted to SiO 2 The silica-based inorganic binder is externally added in an amount within a range of 0.5 to 5% by volume.

[0076] According to the research of the inventors, in the composition of the aluminum composite material containing metal and / or ceramic and graphite, if the graphite powder is less than 40% by volume, the amount of graphite powder is too small, so the thermal conductivity of the composite material becomes low, and the material with high thermal conductivity as the target of the present invention cannot be obtained. On the other hand, if it is more than 80% by volume, the strength of the composite material becomes low. Therefore, the graphite composite material of the present invention needs to contain graphite powder in the range of 40 to 80% by volume. In addition, according to the research of the inventors, when the total amount of metal powder and / or ceramic powder is less than 6% by volume, the effect of improving the strength of the bending strength of 90 MPa or more, which is one of the targets of the present invention, cannot be obtained in the composite material. On the other hand, when the total amount of metal powder and / or ceramic powder exceeds 45% by volume, the thermal conductivity of the composite material sometimes becomes low. For these reasons, the graphite composite material of the present invention needs to contain metal powder and / or ceramic powder in the range of 6 to 45% by volume in total.

[0077] <Method for producing the graphite composite material of the present invention>

[0078] Next, the method for producing the graphite composite material of the present invention is described. According to the production method of the present invention, the excellent graphite composite material of the present invention described above can be easily obtained. The production method of the present invention is characterized in that it has the following molding process and compounding process. In the molding process of the molding, for the molding used in the compounding, a silica-based inorganic binder is added in the range of 0.5 to 5 parts by volume to 100 parts by volume (including voids) of a mixed powder of raw materials adjusted in a manner such that graphite powder is 40 to 80% by volume, the total amount of metal powder and / or ceramic powder is 6 to 45% by volume, the voids after molding are 13 to 50% by volume, and the total is 100% by volume, and a molding is formed with the obtained mixed material, and the molding is heat-cured at a temperature of 100°C to 1100°C to prepare a molding with voids for compounding. In the above-mentioned heat curing, in order to prevent oxidation of the graphite powder used, it is preferred to heat and cure in a nitrogen or inert atmosphere as needed.

[0079] In the next composite process, a molten aluminum metal or the like is infiltrated or pressed into the voids of the molded body obtained in the molding process of the molded body at a pressure of 20 to 200 MPa, so that the molded body and the aluminum metal or the like are composited. As a result, a graphite composite material with excellent properties can be easily obtained, wherein the graphite composite material is composed of: the aforementioned graphite powder is contained in a range of 40 to 80 volume %, the aforementioned aluminum metal or the like is contained in a range of 13 to 50 volume %, the aforementioned metal powder and / or the aforementioned ceramic powder is contained in a range of 6 to 45 volume %, the total amount of these materials is set to 100 volume %, and the SiO converted into an external addition is added. 2 The aforementioned silica-based inorganic binder is 0.5 to 5 volume %, the bending strength of the graphite-based composite material is above 90 MPa, and the thermal conductivity in any direction of the XY direction or the Z direction is above 240 W / m·K, and further, the thermal expansion coefficient in any direction of the XY direction or the Z direction is below 6.0 ppm / K.

[0080] Hereinafter, each step of the method for producing the graphite composite material of the present invention will be described in detail.

[0081] (1) Molding process of molded product (preform)

[0082] As described above, in the manufacturing method of the present invention, first, the final graphite composite material is adjusted to an appropriate amount so that the graphite powder is in the range of 40 to 80 volume %, and the metal powder and / or ceramic powder is in the range of 6 to 45 volume % in total, and the mixture is mixed and mixed. A silica-based inorganic binder is externally added in the range of 0.5 to 5 volume parts relative to a total of 100 volume parts of the mixed powder material and voids as the raw materials, and the obtained material is used to form a molded product for making a molded body. Then, the obtained molded product is heat-cured at a temperature of 100°C to 1100°C to prepare a molded product (preformed product) for composite. There is no particular limitation on the method for forming the molded product before heat curing, and various methods such as compression molding methods such as press molding, filter press pressing, roll molding, CIP molding, and sedimentation method, and casting molding into a plaster mold can be used.

[0083] By controlling the molding pressure of the compression molding performed by the above-mentioned method, the porosity of the molded body before composite can be controlled. For example, a molded body with a void of 15 to 50% by volume is obtained in the usual press molding. Therefore, according to the manufacturing method of the present invention, graphite powder and metal powder and / or ceramic powder can be mixed in 50 to 85% by volume except for the voids, so it has the advantage of easy material design. In addition, according to the manufacturing method of the present invention, in the molding process of the above-mentioned molded body, the use ratio of graphite powder and metal powder and / or ceramic powder as the material of the molded body can be easily appropriated, so that the final graphite composite material obtains the desired high strength, high thermal conductivity and low thermal expansion coefficient as the target of the present invention. Furthermore, by controlling the type, amount and molding pressure of the silica-based inorganic binder used in the manufacturing method of the present invention, the amount of voids in the molded body (preform) of the aluminum part of the composite material can be easily appropriated, and the composite material is obtained by infiltrating and composited with a molten aluminum metal or the like in the next composite process described later.

[0084] In the molding step of the composite molded body (preform) constituting the manufacturing method of the present invention, as described above, it is characterized in that the amount of the composite molded body (preform) converted into SiO is 100 parts by volume relative to the total of 100 parts by volume of the mixed powder of the graphite powder and the metal powder and / or ceramic powder as raw materials and the voids thereof. 2A silica-based inorganic binder is externally added in the range of 0.5 to 5 parts by volume, and a molded article is formed from the obtained material. The binder used at this time needs to be a silica-based inorganic binder. Examples of silica-based inorganic binders include colloidal silica, ethyl silicate, silicone resin, and water glass composed of sodium silicate, all of which can be preferably used. The amount of the silica-based inorganic binder added in the manufacturing method of the present invention is 100 parts by volume of the total of the mixed powder as the raw material and its voids, converted into SiO 2 The amount is 0.5 to 5 parts by volume. It is preferably added in an amount of 1.0% or more and 5% or less on a volume basis. According to the research of the inventors, if it is less than 0.5 parts by volume, the effect of adding the inorganic binder cannot be fully obtained. In addition, if more than 5 parts by volume are added, the mixing ratio of graphite and other raw materials becomes relatively small, and thermal conductivity may be impaired.

[0085] According to the research of the inventors, the addition of a silica-based inorganic binder is necessary for the good forming of a molded object using a mixed powder material, and further, for maintaining the shape of a molded body after the obtained molded object is heated and solidified (calcined). The graphite powder with a crystal structure constituting the graphite-based composite material obtained by the manufacturing method of the present invention is in a layered, three-dimensional mesh structure, so that especially when a molded object is formed by a compression molding method, the force for restoring the molded object or the molded body, the so-called rebound, is large. Therefore, adding a silica-based inorganic binder to the material for making the molded body specified in the present invention becomes an important condition for maintaining the shape of the molded body in a good state for the molded object obtained in the molding process of the aforementioned molded body, and further for the molded body after the molded object is heated and solidified.

[0086] In the manufacturing method of the graphite composite material of the present invention, when adding an inorganic binder, an organic binder can also be used in combination. At this time, the addition amount of the organic binder is preferably less than 5 parts by mass. For example, thermosetting resins such as tar pitch and phenolic resin can be used as organic binders. Organic binders can be added as auxiliary materials during forming such as compression molding, but since they disappear during pre-firing, it is necessary to use inorganic binders in the manufacturing method of the present invention in which the shape of the molded body after pre-firing is maintained as an important issue.

[0087] In the manufacturing method of the present invention, the materials for manufacturing the molded body described above are mixed and stirred in a conventional mixer, and then, as described above, pressure molding is performed using a molding machine such as press molding, filter press pressing, roll molding, or CIP molding. The density of the molded body and the associated voids also vary depending on the molding pressure. For example, when 10 MPa (100 kgf / cm 2 )~200MPa(2000kgf / cm2 ) pressure for press forming, CIP forming, etc. Specifically, for example, for a 60mmφ pressing die, the load is 28kN to 560kN. Thereby, a molded product in good condition with 13 to 50% by volume of voids can be manufactured. As mentioned above, the voids are equivalent to the impregnation portions of aluminum metal, etc. formed in the next step, so the control of the molding pressure is important for obtaining the desired infiltration rate of aluminum metal, etc. The molded product formed as described above is heat-cured at a temperature of 100 to 1100°C in air or, as needed, in an inactive atmosphere such as nitrogen and argon, and in the next compounding step, it becomes a molded body (preform) in good condition for high-pressure infiltration of a molten aluminum metal, etc.

[0088] (2) Process for preparing (compounding) graphite composite materials

[0089] In the manufacturing method of the present invention, a molten aluminum metal or the like is infiltrated into a molded body (preformed body) having 13 to 50% by volume of voids prepared as above, and the molten aluminum metal or the like is filled in the aforementioned voids, and then solidified and composited to obtain the graphite composite material of the present invention. The method of infiltrating the molten aluminum metal or the like into the voids of the aforementioned molded body is not particularly limited, and for example, a method of high-pressure infiltration using an extrusion casting, a die casting, or a high-pressure press can be used. The infiltration pressure at this time varies depending on the density of the molded body (preformed body) prepared as described above, its porosity, and the particle size of the graphite powder, metal powder, and / or ceramic powder used in the preparation of the molded body. According to the research of the inventors, the range of 20 to 200 MPa, and further 30 to 200 MPa is appropriate. When it is lower than 20 MPa, the infiltration pressure is low, and sometimes the infiltration of the aluminum metal or the like is insufficient, so it is not preferred. On the other hand, even if the pressure exceeds 200 MPa, the impregnation of aluminum metal or the like is completed. However, considering the energy consumption, the life of the mold, etc., an impregnation pressure of 200 MPa or less is sufficient.

[0090] Example

[0091] Hereinafter, the present invention will be specifically described based on the examples and comparative examples, but the present invention is not limited to these examples. It should be noted that the "%" in the examples and comparative examples is based on volume % unless otherwise specified, and the "parts" is based on volume unless otherwise specified. The volume % is calculated from the mass ratio of the raw material powders used, the specific gravity of each material such as graphite, and the desired amount of voids in the formed molded body. The amount of the silica inorganic binder is the volume % of external addition when the total amount of the mixed powder specified in the present invention as the main raw material and the aluminum metal (impregnated into the voids of the molded body) is set to 100 volume %. The composition and characteristic values ​​of the graphite-containing aluminum composite materials of each example and comparative example are summarized in Table 1-1 and Table 1-2.

[0092] [Example 1]

[0093] In this example, as graphite powder, two kinds of artificial graphites, artificial graphite CGB-90 (trade name, average particle size 90 μm) and artificial graphite CGB-8R (trade name, average particle size 8 μm) manufactured by Nippon Graphite Industries, Co., Ltd., were mixed and used. The crystal structures of these artificial graphites were confirmed by X-ray diffraction measurement, and the results showed that all of them had layered graphite crystals.

[0094] Specifically, as graphite powder, 30 parts of artificial graphite with an average particle size of 8 μm and 70 parts of artificial graphite with an average particle size of 90 μm were mixed and used. Then, 100 parts (specific gravity: 2.2) of the two kinds of graphite mixed above and 43 parts (specific gravity: 3.2) of SiC powder with an average particle size of 4 μm as ceramic powder were mixed to form SiO 2 Ethyl silicate solution was added as an inorganic binder in an amount equivalent to 1.2% by volume, and the mixture was mixed thoroughly in a mixer. The mixture was placed in a 60 mm φ mold and heated at 80 kgf / cm 2 The molded body (preform) was pressed under a load of , and calcined (pre-calcined) in an air atmosphere at 400°C for 1 hour to obtain a molded body (preform) with a void content of 22%.

[0095] The molded body with voids obtained above was heated to 500°C and loaded into a press, and a molten aluminum alloy of AC3A at 730°C was infiltrated under high pressure at a pressure of 50 MPa using a high pressure press to obtain a composite material of this example in which the voids of the molded body were infiltrated with the aluminum alloy. As shown in Table 1-1, the composition of the aluminum composite material containing ceramic and graphite obtained in the above composite process is 60% graphite, 18% SiC, and 22% aluminum alloy in volume ratio, totaling 100%, and SiO is added externally. 2The inorganic binder content is 1.2%.

[0096] The composite material of this example obtained above is a high-strength and high-thermal-conductivity composite material having a bending strength of 120 MPa, a thermal conductivity of 390 W / m·K in the XY direction, 80 W / m·K in the Z direction, and an average of 235 W / m·K. In addition, regarding its thermal expansion coefficient, it is 5.5 ppm / K in the XY direction, 13.5 ppm / K in the Z direction, and an average of 9.5 ppm / K. The obtained results are summarized in Table 1-2. It can be seen that the composite material (raw material) of the above-mentioned structure is a raw material with high strength, high thermal conductivity, and low thermal expansion coefficient, for example, it can be suitable for use in power module bases, heat sinks, etc. In particular, the composite material (raw material) of this example has a small thermal expansion coefficient in the XY direction as described above, so it is possible to be used for silicon semiconductor element bases, silicon carbide semiconductor element bases, gallium nitride semiconductor element bases, etc. with low thermal expansion coefficients.

[0097] The bending strength of the composite material is measured by a three-point bending test using a 3×4×40 mm test piece made according to JIS R 1601. In addition, for the thermal conductivity, a 10 mm φ, 2 mm thick test piece is made and measured by a laser flash method. The laser flash method used in the determination of thermal conductivity is measured with reference to JIS R 1611 for ceramics. The thermal expansion coefficient is measured using a push rod type thermal dilatometer TMA-60 (trade name, manufactured by Shimadzu Corporation). All measurements are made at 25°C (room temperature). In addition, other examples are measured in the same manner.

[0098] [Examples 2 to 4]

[0099] As shown in Table 1-1, a desired amount of SiC powder (average particle size: 4 μm), AlN powder (average particle size: 3 μm, specific gravity: 3.3), or alumina powder (average particle size: 5 μm, specific gravity: 4.0) was added to a mixed graphite powder of the same composition as used in Example 1, and molded bodies (preformed bodies) having voids were prepared by the same method as in Example 1. The obtained molded bodies (preformed bodies) were in a good state with voids of 15%, 22%, and 25%, respectively. Next, in a composite process using the same pressing machine as in Example 1, the same AC3A aluminum alloy melt as used in Example 1 was impregnated into the obtained molded bodies having voids, and aluminum composite materials containing ceramic and graphite of Examples 2 to 4 were prepared. Table 1-1 shows the material composition of each obtained composite material and the results of the measured bending strength.

[0100] In addition, the same evaluation test was performed on the obtained aluminum composite materials containing ceramic and graphite in the same manner as in Example 1, and the obtained evaluation results are summarized in Table 1-2. As shown in Table 1-2, it was confirmed that the graphite composite materials of Examples 2 to 4 were all materials having a bending strength of 90 MPa or more and showing high strength, a thermal expansion coefficient of 6 ppm / K or less in the XY direction, and a thermal conductivity of 240 W / m·K or more in the XY direction, and showing high strength, high thermal conductivity, and low thermal expansion coefficient as the target of the present invention.

[0101] [Example 5]

[0102] In this example, as graphite powder, F#2 (trade name, average particle size 130 μm) manufactured by Nippon Graphite Industries, Co., Ltd., which is a natural graphite powder having a layered crystal structure, was used. Then, 27 parts of Si powder (specific gravity: 2.3) with an average particle size of 45 μm as metal powder and SiO as an inorganic binder were added to 100 parts of the natural graphite powder. 2 The ethyl silicate solution was converted into an amount equivalent to 1.5%, and a molded body (preformed body) having 22% of voids was prepared in the same manner as in Example 1. Then, the molten aluminum alloy was infiltrated into the obtained molded body using a high pressure press using the same method and materials as in Example 1 to obtain a total of 100 volume % of graphite 62%, Si powder 16%, and aluminum alloy 22%, and SiO was added externally. 2 An aluminum composite material containing Si metal and graphite having a composition in which an inorganic binder content is 1.5%.

[0103] The aluminum-containing composite material containing Si metal and graphite obtained as described above was subjected to the same evaluation test in the same manner as in Example 1, and the evaluation results obtained are shown in Table 1-2. As shown in Table 1-2, the bending strength of the graphite-based composite material of this example is 95 MPa, which is high strength. In addition, regarding the thermal conductivity, it is 394 W / m·K in the XY direction, 70 W / m·K in the Z direction, and the average thermal conductivity is 232 W / m·K. In addition, regarding the thermal expansion coefficient, it is 3.6 ppm / K in the XY direction, 16.7 ppm / K in the Z direction, and the average is 10.2 ppm / K. In this way, the composite material of this example is an aluminum composite material containing Si metal and graphite that shows high strength and high thermal conductivity, and further low thermal expansion coefficient. In particular, the thermal expansion coefficient in the XY direction is as low as 3.6 ppm / K, which confirms that it shows a good low thermal expansion coefficient.

[0104] [Example 6]

[0105] In this example, the same natural graphite powder as used in Example 5 was used as graphite powder. Then, 50 parts of titanium powder (specific gravity: 4.5) with an average particle size of 55 μm as metal powder was added to 100 parts of the natural graphite powder, and a molded body (preformed body) in good condition with 21% of voids was prepared by the same method as in Example 1. Then, the molten aluminum alloy was infiltrated into the obtained molded body by a high pressure press using the same method and materials as in Example 1, and a total of 100 volume% of graphite 59%, titanium 20%, and aluminum alloy 21% was obtained, and SiO was added externally. 2 The aluminum composite material containing titanium metal and graphite of this example has a composition having an inorganic binder content of 1.2%.

[0106] The aluminum composite material containing titanium metal and graphite obtained as described above was subjected to the same evaluation test in the same manner as in Example 1, and the obtained evaluation results are shown in Table 1-2. As shown in Table 1-2, the bending strength of the composite material obtained above was 130 MPa, which was high strength, and the thermal conductivity was 265 W / m·K in the XY direction, 114 W / m·K in the Z direction, and the average thermal conductivity was 189 W / m·K. In addition, the thermal expansion coefficient was 4.6 ppm / K in the XY direction, 16.0 ppm / K in the Z direction, and the average was 10.3 ppm / K. Thus, the composite material of this example is an aluminum composite material containing titanium metal and graphite that exhibits high strength, high thermal conductivity, and low thermal expansion coefficient.

[0107] [Example 7]

[0108] The mixed material prepared by mixing the same materials as those used in Example 1 in the same proportion was placed in a vacuum bag and, after suction, was heated at 200 kgf / cm 2 The molded body was CIP-formed (cold isostatic pressing) at a pressure of 50 MPa to obtain a molded body (preform) with uniform density, less directional content, and 19% voids. The molded body was impregnated with the same aluminum alloy melt as used in Example 1 at a pressure of 50 MPa using the same high-pressure press as used in Example 1 to obtain an aluminum composite material containing ceramic and graphite. The composite material is 62% graphite, 19% SiC, and 19% aluminum alloy, totaling 100% by volume, and SiO is added externally. 2 The composite material has a composition converted to 1.5% of an inorganic binder.

[0109] The aluminum composite material containing ceramics and graphite obtained as described above was subjected to the same evaluation test by the same method as that performed in Example 1, and the evaluation results obtained are shown in Table 1-2. The thermal conductivity of the composite material obtained above is 250 KW / m·K in the XY direction and 220 KW / m·K in the Z direction, and it is a composite material containing ceramics, graphite and aluminum having thermal conductivity close to that in the XY direction and the Z direction. It is believed that this is because, if the molded body (preformed body) is isotropically compressed and molded by CIP molding, the graphite as a layered structure is randomly oriented, and as a result, the direction of thermal conduction of the obtained composite material also becomes random. The bending strength of the composite material obtained above is 130 MPa, showing high strength. In addition, regarding the thermal expansion coefficient, it is 5.8 ppm / K in the XY direction, 9.3 ppm / K in the Z direction, and 7.6 ppm / K on average.

[0110] [Example 8]

[0111] In this example, as graphite powder, F#2 (trade name, average particle size 130 μm) which is a natural graphite powder having a layered crystal structure is used in the same manner as in Example 5. Then, 30 parts of Si powder having an average particle size of 45 μm as metal powder and a desired amount of the following silicone resin solution as a silica-based inorganic binder are added to 100 parts of the natural graphite powder to prepare a molded body (preformed body) having voids. The silicone resin solution used in the above is a 20w% resin solution prepared by dissolving KR-220 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) in isopropyl alcohol (IPA). In this example, SiO 2 An amount corresponding to 2.0% was added to the resin solution.

[0112] In this example, when a molded body (preform) having voids was produced, a load of 75 kN (270 kgf / cm 2 ) was pressed and pre-fired in the same manner as in Example 1 to obtain a molded body (preformed body) in a good state with a void content of about 17%. Then, using the same method and materials as in Example 1, a molten aluminum alloy was infiltrated into the obtained molded body using a high pressure press to obtain a total of 100 volume % of graphite 65%, Si powder 18%, and aluminum alloy 17%, and SiO was added externally. 2 An aluminum composite material containing Si metal and graphite having a composition in which an inorganic binder content is 2.0%.

[0113] The composite material of this example obtained above is a high-strength composite material with a bending strength of 150 MPa, a thermal conductivity of 450 W / m·K in the XY direction, 130 W / m·K in the Z direction, and an average of 290 W / m·K. In addition, regarding its thermal expansion coefficient, it is 3.2 ppm / K in the XY direction, 14.4 ppm / K in the Z direction, and an average of 8.8 ppm / K. In this example, the pressing pressure when preparing the molded body by press molding is made stronger than that in Example 1, and the effect of adding the silica-based inorganic binder is further exerted, the molded body does not rebound, and a composite body with a high volume ratio of graphite powder and Si metal powder is obtained.

[0114] [Example 9]

[0115] In this example, 100 parts of two kinds of artificial graphites were mixed in the same manner as in Example 1, and 37 parts of titanium powder as metal powder, 40 parts of SiC powder as ceramic powder, and ethyl silicate solution as a silica-based inorganic binder were used, with the ratio of SiO2 to the main raw material being 1:1. 2 The raw materials were mixed by external addition in the form of 1.2% conversion. Then, the prepared mixed raw materials were molded and pre-sintered in the same manner as in Example 1 to produce a molded body (preform) having 20% ​​of voids. The voids of the obtained molded body (preform) were infiltrated with aluminum alloy by high pressure pressing using the same materials and operations as in Example 1.

[0116] As a result, the composite material of this example obtained above is a composite material having high strength, with a bending strength of 135 MPa, and a thermal conductivity of 380 W / m·K in the XY direction, 115 W / m·K in the Z direction, and an average of 247 W / m·K. In addition, regarding its thermal expansion coefficient, it is 5.5 ppm / K in the XY direction, 14.0 ppm / K in the Z direction, and an average of 9.8 ppm / K. From the above results, it was confirmed that a useful composite material showing high strength, high thermal conductivity, and low thermal expansion coefficient can be obtained by using a combination of metal powder and ceramic powder and adding them in a desired amount.

[0117] [Comparative Example 1]

[0118] In this example, as graphite powder, two kinds of artificial graphites having the same composition as that used in Example 1 but different average particle sizes were used in combination. Then, as shown in Table 1-1, unlike in the example, a molded body (preformed body) was prepared in the same manner as in Example 1, and a graphite-containing aluminum composite material for comparison was obtained using the molded body. Specifically, as in Example 1, SiO 2A graphite material was obtained by converting an amount of ethyl silicate solution equivalent to 1.2%, and a molded body (preform) was prepared using the obtained graphite material by the same operation as in Example 1. As a result, the obtained molded body (preform) was in a good state, but the voids were 12%, which was less than the molded body (preform) of Example 1. In the same manner as in Example 1, the obtained molded body was impregnated with the same aluminum alloy melt at a pressure of 50 MPa using a high-pressure press to obtain a comparative graphite-containing aluminum composite material.

[0119] As shown in Table 1-1, the composition of the graphite-containing aluminum composite material of Comparative Example 1 obtained as described above is 88% graphite, 12% aluminum alloy, and a total of 100%, and SiO 2 The amount of the inorganic binder was calculated to be 1.2%. The graphite-containing aluminum composite material obtained as described above was subjected to the same evaluation test as in Example 1, and the obtained evaluation results are shown in Table 1-2.

[0120] As shown in Table 1-2, the thermal conductivity of the composite material obtained above is 410 W / m·K in the XY direction, 75 W / m·K in the Z direction, and 243 W / m·K on average, showing high thermal conductivity. In addition, regarding the thermal expansion coefficient, it is 3.6 ppm / K in the XY direction, 15.1 ppm in the Z direction, and 9.4 ppm / K on average, showing small values ​​similar to the examples. However, the bending strength is as low as 25 MPa, and it is not a high-strength composite material with a bending strength of more than 90 MPa as the target of the present invention. It is believed that the reason why the strength of the composite material of Comparative Example 1 becomes extremely low as described above is that metal powder and ceramic powder are not used as the forming material of the molded body, and the amount of graphite becomes too high, which is 88%.

[0121] [Comparative Examples 2 to 4]

[0122] In Comparative Examples 2 to 4, as graphite powder, two kinds of artificial graphites having layered graphite crystals that are the same as those used in Example 1 and are homogeneous except for the difference in average particle size are used, and are mixed in desired amounts. As shown in Table 1-1, in Comparative Examples 2 and 3, SiC powder (average particle size: 4 μm) is used as ceramic powder in amounts outside the range specified in the present invention, and in Comparative Example 4, the total amount of metal powder and ceramic powder is more than the amount specified in the present invention. Then, except for the above, a molded body (preformed body) is prepared by the same operation as in Example 1. In the same manner as in Example 1, the same aluminum alloy melt as used in Example 1 is infiltrated into the obtained molded body by a high-pressure press at a pressure of 50 MPa to obtain aluminum-containing composite materials containing metal / or ceramic and graphite of Comparative Examples 2 to 4 of each composition.

[0123] The composite materials of Comparative Examples 2 to 4 obtained as described above were subjected to the same evaluation test by the same method as that performed in Example 1, and the obtained evaluation results are shown in Table 1-2. As shown in Table 1-2, the composite materials of Comparative Examples 2 to 4 obtained above are not composite materials that can achieve the purpose of the present invention in the following aspects. First, as in the composite material of Comparative Example 2, when the amount of ceramic powder added is less than that specified in the present invention, although the strength is slightly improved compared with the composite material of Comparative Example 1 in which neither ceramic powder nor metal powder is used, the flexural strength of the composite material is 40 MPa, which is not practical.

[0124] On the other hand, the composite materials of Comparative Examples 3 and 4 have a composition in which the total amount of metal and / or ceramic is greater than the range specified in the present invention, as shown in Table 1, and therefore the amount of graphite powder is less than the range specified in the present invention. It is understood that in the case of the composite materials of Comparative Examples 3 and 4 having such a composition in which the total amount of metal and / or ceramic is excessive, the strength cannot reach 90 MPa or more, which is not sufficient, and further the thermal conductivity is low, and it is not possible to become a material showing the high thermal conductivity specified as the goal of the present invention.

[0125] [Comparative Example 5]

[0126] As the graphite powder raw material and the ceramic powder raw material, the same artificial graphite powder and SiC powder as used in Example 1 were used to form a raw material composition without adding an inorganic binder. The composite material of this example was produced by the same operation as in Example 1. As a result, the composite material obtained in Comparative Example 5 had a larger amount of aluminum alloy than the composite material obtained in Example 1. It is believed that the reason is that since no inorganic binder was added, the molded body (preformed body) rebounded during press molding and then calcination, and the voids in the molded body increased. The thermal conductivity of the composite material obtained in Comparative Example 5 is lower than the thermal conductivity specified in the present invention, and the thermal expansion coefficient is larger than the thermal expansion coefficient targeted in the present invention. In addition, the bending strength is low and does not reach the value of more than 90 MPa targeted in the present invention, and all do not meet the properties targeted in the present invention.

[0127] [Table 1-1]

[0128] Table 1-1: Preparation conditions and flexural strength of composite materials of Examples and Comparative Examples

[0129]

[0130] ·Mass ratio of two types of artificial Gr (artificial graphite):

[0131] 30 parts of artificial Gr with an average particle size of 8 μm and 70 parts of artificial Gr with an average particle size of 90 μm on a mass basis

[0132] ·Amount of silica-based inorganic binder: The outer SiO 2 Volume%

[0133] In 100 parts of the raw material mixed powder, SiO 2 This is equivalent to 2.5 parts of ethyl silicate solution or 20w% IPA solution of silicone.

[0134] [Table 1-2]

[0135] Table 1-2: Properties of composite materials of Examples and Comparative Examples

[0136]

Claims

1. An aluminum composite material containing metal and / or ceramic and graphite, characterized in that: It is an aluminum composite material containing metal and / or ceramic and graphite, which is formed by compounding a molded body with voids using a molten aluminum metal or aluminum alloy, wherein the molded body with voids is formed by mixed powder and a silicon dioxide-based inorganic binder is added, wherein the mixed powder comprises: graphite powder, which is composed of natural graphite powder having a non-amorphous crystal structure or artificial graphite powder having a non-amorphous crystal structure; and at least one of metal powder and / or ceramic powder, The aluminum composite material containing metal and / or ceramic and graphite contains the graphite powder in the range of 40 to 80 volume %, the aluminum metal or aluminum alloy in the range of 13 to 50 volume %, the metal powder and / or the ceramic powder in the range of 6 to 45 volume % in total, the total amount of these materials is set to 100 volume %, and the silicon dioxide-based inorganic binder is externally added in an amount of 0.5 to 5 volume % converted to SiO2, The aluminum composite material containing metal and / or ceramic and graphite has a bending strength of 90 MPa or more, a thermal conductivity of 240 W / m·K or more in any of the XY direction or the Z direction, and a thermal expansion coefficient of 6.0 ppm / K or less in any of the XY direction or the Z direction.

2. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1, wherein: The thermal conductivity in the XY direction is 240 W / m·K or more, and the thermal conductivity in the Z direction is 50 W / m·K or more, the thermal expansion coefficient in the XY direction is 6 ppm / K or less, and the thermal expansion coefficient in the Z direction is 19 ppm / K or less.

3. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1, wherein: The thermal expansion coefficient in the XY direction is greater than or equal to 3 ppm / K and less than or equal to 6 ppm / K.

4. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1 or 2, wherein: The silica-based inorganic binder includes at least one selected from the group consisting of colloidal silica, ethyl silicate, water glass, and silicone resin.

5. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1 or 2, wherein: The average particle size of the graphite powder is 3 μm to 300 μm.

6. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1 or 2, wherein: The non-amorphous crystal structure is any one crystal structure selected from the group consisting of layered crystals, three-dimensional graphite crystals, diamond crystals, and fullerene structures.

7. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1 or 2, wherein: The average particle size of the metal powder and / or the ceramic powder is 0.5 to 200 μm.

8. The aluminum composite material containing metal and / or ceramic and graphite according to claim 1 or 2, wherein: The metal powder is any one selected from the group consisting of silicon powder, titanium powder, silver powder, copper powder, iron powder, stainless steel and aluminum powder, and the ceramic powder is any one selected from the group consisting of alumina powder, silicon nitride powder, silicon carbide powder and aluminum nitride powder.

9. A method for producing an aluminum composite material containing metal and / or ceramic and graphite, characterized in that: It has: A molding step of a molded body, wherein a silicon dioxide-based inorganic binder is added in an amount of 0.5 to 5 parts by volume of a mixed powder of raw materials adjusted to 100 parts by volume of a raw material composed of natural graphite powder having a non-amorphous crystal structure or artificial graphite powder having a non-amorphous crystal structure, graphite powder having a total amount of 6 to 45% by volume, metal powder and / or ceramic powder having a total amount of 13 to 50% by volume, and voids in the molded body after molding, and the total amount of the raw material is 100% by volume, and the obtained material is used to form a molded body, and the molded body is heated and cured at a temperature of 100° C. to prepare a molded body having the voids for composite formation; and A composite step of infiltrating or pressing a molten aluminum metal or aluminum alloy into the voids of the molded body at a pressure of 20 to 200 MPa to perform composite formation; A composite material is manufactured having a bending strength of 90 MPa or more, a thermal conductivity of 240 W / m·K or more in either the XY direction or the Z direction, and a thermal expansion coefficient of 6.0 ppm / K or less in either the XY direction or the Z direction.

10. The method for producing an aluminum composite material containing metal and / or ceramic and graphite according to claim 9, wherein: The silica-based inorganic binder includes at least one selected from the group consisting of colloidal silica, ethyl silicate, water glass, and silicone resin.

11. The method for producing an aluminum composite material containing metal and / or ceramic and graphite according to claim 9 or 10, wherein: The method performed in the molding step of the molded body is at least any one selected from the group consisting of press molding, filter press pressing, roll molding, CIP molding, sedimentation method and casting molding.

Citation Information

Patent Citations

  • JP1975061018A

  • Method of forming waterrproof shield into soil using nozzle and apparatus for executing same

    JP1977008616A

  • Preparation of diterpene

    JP1978068766A

  • Electrode material for electrical discharge machining

    JP2004209610A